Recent Advances of Microfluidic Platforms for Controlled Drug Delivery in Nanomedicine - Ejeta F (Dove Medical Press, 2021)
Fikadu Ejeta Department of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, Mizan-Tepi University, Mizan-Aman, EthiopiaCorrespondence: Fikadu Ejeta Tel +251910136034Email fikaduejeta@gmail.comAbstract: Nanomedicine drug delivery systems hold great potential for the therapy of many diseases, especially cancer. However, the controlled drug delivery systems of nanomedicine bring many challenges to clinical practice. These difficulties can be attributed to the high batch-to-batch variations and insufficient production rate of traditional preparation methods, as well as a lack of technology for fast screening of nanoparticulate drug delivery structures with high correlation to in vivo tests. These problems may be addressed through microfluidic technology. Microfluidics, for example, can not only produce nanoparticles in a well-controlled, reproducible, and high-throughput manner, but it can also continuously create three-dimensional environments to mimic physiological and/or pathological processes. This overview gives a top-level view of the microfluidic devices advanced to put together nanoparticulate drug delivery systems, including drug nanosuspensions, polymer nanoparticles, polyplexes, structured nanoparticles and therapeutic nanoparticles. Additionally, highlighting the current advances of microfluidic systems in fabricating the more and more practical fashions of the in vitro milieus for fast screening of nanoparticles was reviewed. Overall, microfluidic technology provides a promising technique to boost the scientific delivery of nanomedicine and nanoparticulate drug delivery systems. Nonetheless, digital microfluidics with droplets and liquid marbles is the answer to the problems of cumbersome external structures, in addition to the rather big pattern volume. As the latest work is best at the proof-of-idea of liquid-marble-primarily based on totally virtual microfluidics, computerized structures for developing liquid marble, and the controlled manipulation of liquid marble, including coalescence and splitting, are areas of interest for bringing this platform toward realistic use.Keywords: microfluidic, nanomedicine, controlled drug delivery, nanocarriers